고정상 생물막 반응기를 이용한 DMSO 함유폐수의 처리 - 신정훈; 정진영; 정윤철; 손대희 (한국물환경학회, 2003)
The objective of this study was to investigate the performances of the activated sludge and fixed-film biological reactor in treating industry wastewater containing dimethyl sulfoxide [DMSO, (CH3)2SO]. When the influent DMSO concentration increased from 400 mg/L to 800 mg/L at hydraulic retention times from 48 to 24 hours, the soluble TOC removal efficiencies of the activated sludge and fixed-film reactors were in the range of 95.3-97.5% and 96.5-97.6%, respectively. Meanwhile, the TCOD removal efficiency of the activated sludge was in the range of 80.5-98.0%, while that of the fixed-film reactor was 94.9-98.5%. The reason for the high fluctuation of TCOD removal in the activated sludge process was the increase in the SS concentration in the effluent. The sludge washout was caused by the destruction of sludge floc due to the DMSO concentration in the suspended culture. However, the fixed-film reactor showed a stable effluent quality compared to that of the activated sludge reactor during whole operating period.